2012
DOI: 10.1130/ges00737.1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Trace-element analyses of zircons from ash-fl ow tuffs and granitic rocks in the eastcentral Sierran Nevada, combined with U-Pb zircon ages and trace-element abundances in whole rocks, allow us to interpret a shared magmatic heritage for widespread eruption of ash-fl ow tuffs and assembly of a typical Sierran granodioritic to granitic intrusive suite. The tuffs have 5%-15% phenocrysts of quartz, feldspar, biotite, and amphibole, silica contents ranging from 70% to 74%, and have variable alkali abundances but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…We conclude that individual zoned intrusive suites in the California arc may have formed incrementally at a range of flux rates, from as low as <0.001 km 3 /yr to 0.005 km 3 /yr or more, with higher rates having the potential to generate and sustain comparatively large reservoirs of mobile magma. Such a range of flux rates is consistent with evidence that all three known pulses of voluminous intrusion in the Mesozoic California arc (Late Triassic, Middle to Late Jurassic, mid-to Late Cretaceous) were at least locally accompanied by eruption of widespread and locally thick, crystal-poor rhyolitic to crystal-rich dacitic ash-flow tuffs (Saleeby et al, 1990;Fiske and Tobisch, 1994;Schermer and Busby, 1994;Fohey-Breting et al, 2010;Barth et al, 2012). …”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…We conclude that individual zoned intrusive suites in the California arc may have formed incrementally at a range of flux rates, from as low as <0.001 km 3 /yr to 0.005 km 3 /yr or more, with higher rates having the potential to generate and sustain comparatively large reservoirs of mobile magma. Such a range of flux rates is consistent with evidence that all three known pulses of voluminous intrusion in the Mesozoic California arc (Late Triassic, Middle to Late Jurassic, mid-to Late Cretaceous) were at least locally accompanied by eruption of widespread and locally thick, crystal-poor rhyolitic to crystal-rich dacitic ash-flow tuffs (Saleeby et al, 1990;Fiske and Tobisch, 1994;Schermer and Busby, 1994;Fohey-Breting et al, 2010;Barth et al, 2012). …”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…Grimes et al (2015) and Barth et al (2017) have established that zircon compositional ranges reflect specific tectonomagmatic environments. The zircon compositional data from the Ritter Range, combined with data from Saddlebag Lake pendant (Barth et al, 2012), not only provide information about melt evolution but also confirm the compositionally distinct nature of Jurassic melts, consistent with the differences in the whole rock major and trace element data presented above.…”
Section: Zircon Geochemistrysupporting
confidence: 76%
“…Studies of these incompletely preserved volcanic sections are critically important to understanding juvenile volcanic arc evolution and potential linkages between explosive volcanism and assembly of the underlying batholith. Geochemical and geochronological studies of the Sierra Nevada magmatic arc suggest a complex relationship between volcanism and batholith construction that remains controversial and poorly constrained (Barth et al, 2012(Barth et al, , 2013Bateman, 1992;Busby-Spera, 1984;Fiske & Tobisch, 1994;Glazner, 1991;Kistler & Swanson, 1981;Saleeby et al, 1990;Tobisch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Less precise U/Pb methods (ion microprobe and laser-ablation ICPMS) are generally an order of magnitude less precise. For example, Barth et al (2012) found evidence for coeval volcanism and plutonism in the Mesozoic Sierran arc, but uncertainties on their ages of ±2 Ma (or more) are far too large to make a definite genetic link between systems that are known to crystallize zircon on timescales an order of magnitude shorter. Zimmerer and McIntosh (2013) obtained laser-ablation ICPMS geochronologic data for volcanic and plutonic rocks of the Oligocene Organ caldera of New Mexico and also concluded that extrusive and intrusive rocks were coeval within *600 ka.…”
Section: Geochronologic Tests For the Link Between Plutons And Large-mentioning
confidence: 97%